2017
DOI: 10.5897/ajar2016.11314
|View full text |Cite
|
Sign up to set email alerts
|

Correlation and cluster analysis of white seeded sesame (Sesamum indicum L.) genotypes oil yield in northern Ethiopia

Abstract: The experiment was carried out to access the inter relationship of genotypes in their oil yield with seed yield, oil content and other yield components and to determine cluster of white seeded sesame genotypes and environments based on their oil yield. Seventeen sesame genotypes were tested at six environments in northern Ethiopia during 2015 main season. The experiment was laid out in Randomized Complete Block Designs (RCBD) with three replications across all the environments. Seed yield had a significant and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 7 publications
5
2
0
Order By: Relevance
“…This indicated that the large influence of environment causing most of the variation in yield performance of sesame genotypes across all locations while the contribution of GEI to the total variation showed minimal role. Similar result was reported on sesame by Mekonnen et al (2015), Mohammed (2015) and Yirga (2016) (Table 4).…”
Section: Combined Analysis Of Variancessupporting
confidence: 90%
See 1 more Smart Citation
“…This indicated that the large influence of environment causing most of the variation in yield performance of sesame genotypes across all locations while the contribution of GEI to the total variation showed minimal role. Similar result was reported on sesame by Mekonnen et al (2015), Mohammed (2015) and Yirga (2016) (Table 4).…”
Section: Combined Analysis Of Variancessupporting
confidence: 90%
“…Accordingly, nearest to the first concentric circle, the environment Dabanu was the ideal environment to select widely adapted sesame genotypes, whereas, Agbe and Finaruwa were far from the ideal environment and considered as unstable. This result was in line with Yan et al (2000), Yan and Rajcan (2002), Yan et al (2007), Fiseha et al (2015 and Yirga (2016) in sesame and Muez et al (2015) in bread wheat.…”
Section: Evaluation Of Environments Based On the Ideal Environmentsupporting
confidence: 83%
“…There was positive significant association between plant height and the traits such as height to first capsule, branches per plant, capsules/plant and oil content. This results are in consonance with results of Goudappagoudra et al, (2011) There was a positive significant correlation between number of branches and traits like plant height, height to first capsule, number of capsules, 1000 seed weight and oil content the results are in consonance with Yirga (2017) and Atul Singh et al, (2018).…”
Section: Resultssupporting
confidence: 90%
“…1). These results are in accordance with Sudhakar et al, (2007), Sumathi et al, (2007), Yingzhong and Yishou (2002), Engin Yol et al, (2010), Ibrahim andKhidir (2012), Ammara Fazal et al, (2015), Yirga (2017) and Atul Singh et al, (2018).…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation